Állapotfelmérés az Europe Match GmbH telepén - Tóth, Lajos (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The factory wanted to know what state was the equipment in the refuse conveying in. On the indicated machines we have conducted vibration diagnostics. We evaluated the measurement results with the help of the software on a computer. We have detected a flaw in the bearing of the extractor. The vibration quantity was optimal at the biggest motor. All bearings were in good condition. We sent the results to the factory, and recommended modifying the setting of one strap foldings for the interest of the vibration strength. We proposed the correction of the lubri-cant on the bearings.